(3eYGedI GdSLjfGJ aj VhA GdehGKjb GdOhdjI hGdhVY aj OhdI GdEeGQGJ GdYQHjI GdeJMOI (B/s - (3GdedG, aGWeI jhSa CMeOs ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI,s, 2016)
(3jJfGhd cJGH (B((3eYGedI GdSLjfGJ aj VhA GdehGKjb GdOhdjI hGdhVY aj OhdI GdEeGQGJ GdYQHjI GdeJMOI(B) (3hGdPj bGe HJCdjag (B((3GdCSJGPI aGWeI jhSa CMeO GdedG(B) (3aj MhGdj (B(130) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdeSLhfhf(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdHGH GdChd (B: (3GdJYQja HGdeSFhdjI GdLfGFjI dQFjS GdLeghQjI , GdHGH GdKGfj (B: (3GdLQGFe GdeSFhd YfgG QFjS GdLeghQjI , GdHGH GdKGdK (B: (3GJgGe heMGceI QFjS GdLeghQjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B118-127.s
Keywords: (3GdeSLhfhf (B((3bGfhf Ohdj(B)s; (3QDSGA GdLeghQjI s -- (3hVY bGfhfj, bhGfjf, EdNs -- (3GdEeGQGJ GdYQHjI GdeJMOIs; (3GdeSLhfhfs -- (3hVY bGfhfj, bhGfjf, EdN(B.s -- (3GdEeGQGJ GdYQHjI GdeJMOIs